TEKNOLOGI PENDIDIKAN SEBAGAI PEMBELAJARAN YANG EFEKTIF - Yusuf Hadijaya (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
The budget implementation at the North Sumatra State Islamic University (UINSU) as a Public Service Agency (BLU) has been changing in the management paradigm from public administration to public service management. Performance Management is an attempt to synchronize various methodologies such as Strategic Management, Human Resources Management, Strategy Maps, Balanced Scorecards, and Financing Management which has a goal to improve performance so that the organization can perform more efficiently and effectively in achieving its institutional goals. Management creates the values required in building a creative and productive organizational culture. The purpose of this study was to analyze the BLU budget implementation from the Performance Management perspective. This study used qualitative research methods. Data collection techniques are conducted by interview, observation, and documents study. The results of this research showed that the budget implementation at the UINSU adjusted to the demands for improving the performance and productivity of Higher Education based on the achievement of the 2016-2020 Strategic Plan (Renstra) at the university in aspects of teaching, research, and society dedication, service quality, and lecturer and education staff productivity, student satisfaction, and financial performance.